Gastritis drug prescribing profile at Pharmacy X Bukittinggi - Zulfisa Zulfisa; Muhajri Agusfina; Renatalia Fika; Annisa Lufiah Safitri; Mevy Trisna (Science Midwifery, 2023)
Gastritis is an inflammatory process or health disorder caused by irritating and infectious factors in the gastric mucosa and submucosa. This study is to evaluate gastritis drug classes, single and combination drugs, age and gender prescribed at Pharmacy X Bukittinggi. The research design used in this research is descriptive research through a restrospective research process. Sampling by purposive sampling. Based on research on the Gastritis Drug Prescribing Profile at Pharmacy X Bukittinggi with the most gastritis sufferers were female patients 215 prescriptions (64.7%). The age most affected by gastritis is in the elderly 160 prescriptions (48.2%), the group of drugs often used is proton pump inhibitors as many as 169 prescriptions (51%). The most commonly used combination drug group was proton pump inhibitors with sucralfate syrup as many as 69 prescriptions (20.8%).